The radiosensitizing effect of platinum nanoparticles in proton irradiations is not caused by an enhanced proton energy deposition at the macroscopic scale. (7th August 2022) - Behrends, C; Bäcker, C M; Schilling, I; Zwiehoff, S; Weingarten, J; Kröninger, K; Rehbock, C; Barcikowski, S; Wulff, J; Bäumer, C; Timmermann, B
Abstract: Objective. Due to the radiosensitizing effect of biocompatible noble metal nanoparticles (NPs), their administration is considered to potentially increase tumor control in radiotherapy. The underlying physical, chemical and biological mechanisms of the NPs' radiosensitivity especially when interacting with proton radiation is not conclusive. In the following work, the energy deposition of protons in matter containing platinum nanoparticles (PtNPs) is experimentally investigated. Approach. Surfactant-free monomodal PtNPs with a mean diameter of (40 ± 10) nm and a concentration of 300 μg ml −1, demonstrably leading to a substantial production of reactive oxygen species (ROS), were homogeneously dispersed into cubic gelatin samples serving as tissue-like phantoms. Gelatin samples without PtNPs were used as control. The samples' dimensions and contrast of the PtNPs were verified in a clinical computed tomography scanner. Fields from a clinical proton machine were used for depth dose and stopping power measurements downstream of both samples types. These experiments were performed with a variety of detectors at a pencil beam scanning beam line as well as a passive beam line with proton energies from about 56–200 MeV. Main results. The samples' water equivalent ratios in terms of proton stopping as well as the mean proton energy deposition downstream of the samples with ROS-producing PtNPs compared to the samples without PtNPs showed no differences within the experimental uncertainties of about 2%. Significance. This study serves as experimental proof that the radiosensitizing effect of biocompatible PtNPs is not due to a macroscopically increased proton energy deposition, but is more likely caused by a catalytic effect of the PtNPs. Thus, these experiments provide a contribution to the highly discussed radiobiological question of the proton therapy efficiency with noble metal NPs and facilitate initial evidence that the dose calculation in treatment planning is straightforward and not affected by the presence of sensitizing PtNPs.